Oral microbiota and their antibiotic susceptibility in free-living monkeys in Goias State, Brazil: Repercussions for injuries in humans - Albuquerque Sobreira, Elisangela de [UNESP]; Silva Bitencout Braga, Carla Afonso da; Rahal, Sheila Canavese [UNESP]; Ribeiro, Evandro Leao [UNESP]; Oliveira Leao Vasconcelosm, Lara Stefania Netto de [UNESP]; Carneiro, Lilian Carla [UNESP]; Teixeira, Carlos Roberto [UNESP]; Diniz de Almeida, Camila Contin [UNESP]; Haddad Junior, Vidal [UNESP] (Soc Brasileira Medicina Tropical, 2019)
Introduction: Goias State, which is in the midwest region of Brazil, has several urban forests. This fact, along with the expansion of urban areas within the limits of Forest Conservation Units, increases the contact between humans and wildlife, such as capuchin monkeys. The impulsive behavior of these animals and the scarcity of food cause them to vigorously search for food, leading to direct encounters with Park visitors, which can result in scratches and bites and making them potential disseminators of pathogenic microorganisms. Methods: Ten specimens of bearded capuchin monkey (Sapajus libidinosus) were captured at the Onofre Quinan Environmental Park in Anapolis, Goias, Brazil. Samples were collected from the monkeys, and the bacteria and fungi present in the samples were isolated and identified. Then, the identified microorganisms were subjected to antibiotic susceptibility testing. Results: A total of 111 bacteria and 12 fungi were isolated, including two strict anaerobic bacteria of the genus Peptostreptococcus, 109 facultative anaerobic bacteria, and 12 yeasts. Among the facultative bacteria, enterobacteria and Staphylococcus were common. Resistance to tetracycline and ampicillin antibiotics was detected in the enterobacteria. and resistance to tetracycline, erythromycin, and clindamycin was detected in the Staphylococci. The other strains were sensitive to all tested antimicrobials. Cefoxitin showed 100% efficacy in all isolated bacteria. Conclusions: For bites from capuchin monkeys, we recommend performing complete hygiene and antibiotic therapy, according to medical recommendations. Given the 100% effectiveness of cefoxitin, it should be considered for this type of injury, especially in the study region.
Keywords: Capuchin monkey; Bites and stings; Antibiotic; Bacterial infections; Sapajus libidinosus